PENGEMBANGAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN MODEL PICTURE AND PICTURE DI SEKOLAH DASAR - Yulia, Ery Mulat (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
Teachers' ability to use Picture and Picture at SD Negeri 1 Made increased and achievement for students increased after teachers used Picture and Picture at SD Negeri 1 Made.The research subjects were SD Negeri 1 Made teachers, consisting of 6 class teachers and 2 subject teachers. There are 4 female teachers at SD Negeri 1 Made and 4 male teachers. Data collection was carried out through learning documents, observations, interviews and documents. Data analysis was carried out using comparative descriptive techniques. Empirical data shows that there is an increase in the learning process of coaching with peer tutors to improve teachers' abilities in using the Picture and Picture learning model at SD Negeri 1 Made. It can be seen from the pre-cycle that the average teacher's ability in learning was only 25% or 2 teachers, rising to 50% or 4 teachers in cycle I. At the end of cycle II, the ability of SD Negeri 1 Made teachers in the learning process averaged 91.7% from 8 teachers or in the very good category. There is an increase in teachers' ability to use the Picture and Picture learning model at SD Negeri 1 Made. In the pre-cycle there were only 2 teachers or 25%, while in the first cycle there were 4 teachers or 40% and in the second cycle only 7 teachers or 87.5% were in the very good category.